Perbandingan Penggunaan Data Hujan Lapangan Dan Data Hujan Satelit Untuk Analisis Hujan-aliran Menggunakan Model Ihacres - Reza Ahmad Fadhli; Bambang Sujatmoko; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study conducted an analysis of satellite rainfall data utilization as an alternative for hydrological modeling. Reliability of satellite rainfall data for hydrological modeling iscompared to the use of ground rainfall data. Rainfall-runoff modeling in this research is used IHACRES program by taking a case study in the Rokan watershed, Riau Province. IHACRESmodel output was compared and analyzed with the output of IFAS simulation. The length of the data used was four years (2003 - 2006) with the variation in the length of data scheme 1(three year calibration), Scheme 2 (two years calibration) and scheme 3 (one year calibration). The results showed that the use of satellite rainfall data for rainfall-runoff modeling IHACRES is better than using ground rainfall data based on the evaluation of the model accuracy coefficient of efficiency (CE). Such thing was reviewed by assessing the CE parameters that have better value, while the parameters R and VE have relatively similar results. CE value of ground rainfall data scheme 1, Scheme 2 and scheme 3 is 0,659; 0,715 and 1,003. CE value of satellite rainfall data 0,924 and 0,875. In general, based on the CE value of the parameter evaluation accuracy simulation step, the rainfall-runoff modeling IFAS using satellite rainfall data are more reliably than the rainfall-runoff modelingIHACRES that uses ground rainfall data and satellite, the value of CE rainfall-runoff modeling IFAS is 1,652.Keywords: ground rainfall data, IFAS, IHACRES, rainfall-runoff modeling, satellite rainfall data